How much does reduced food intake contribute to cancer-associated weight loss?. Issue 4 (December 2018) - Martin, Lisa; Kubrak, Catherine
Abstract : Purpose of review: An international consensus group defined cancer cachexia as a syndrome of involuntary weight loss, characterized by loss of skeletal muscle (with or without fat loss), which is driven by a variable combination of reduced food intake and altered metabolism. This review presents recent studies that evaluated the contribution of reduced food intake to cancer-associated weight loss. Recent findings: Four studies examined food intake in relation to weight loss. Heterogeneity among studies rendered aggregation and interpretation of results challenging. Despite these limitations, reduced food intake had consistent significant, independent associations with weight loss. However, reduced food intake did not explain all the variation in weight loss; and limited data suggests factors related to alterations in metabolism (e.g. increased resting energy expenditure, systemic inflammation) are also contributing to weight loss. Summary: Reduced food intake is a significant contributor to cancer-associated weight loss. Understanding the magnitude of the association between food intake and weight loss may improve when it is possible to account for alterations in metabolism. Efforts to align clinical assessments of food intake to reduce heterogeneity are needed.